How to Avoid a Climate Disaster, Bill Gates - Summaiya Malik (CISS Insight Journal, 2022)
Bill Gates in his book How to Avoid a Climate Disaster dispenses evidence of impending climate crisis and prescribes solutions to address it. His book factors in insight of researchers and academicians from varying environmental and energy disciplines. More importantly, Gates establishes a sense of urgency about the issues, his subtle humor, and his first-person direct address keeps the reader engaged throughout the book.Bill has been increasingly investing in Breakthrough Energy ventures and Antora Energy. He aims to help decarbonize industries and transport sectors. However, such staunch advocacy of climate change has invited some negative feedback. His expertise on this subject is frequently questioned given that he is a wealthy business magnate who has previously invested in fossil fuel industry. He himself apologetically observes early in the book that "I'm an imperfect messenger on climate change. The world is not exactly lacking in rich men with big ideas about what other people should do."(p. 18) Nonetheless, he also claims that being a technophile, he believes in the potential of technology to tackle the most difficult issues.